Efficiency measures and influencing factors for rural land outsourcing: Evidence from China, 2003–2015 - Wang, Mengdi; Wang, Changzheng; Peng, Xiaobing (Frontiers in Environmental Science, 2022)
In the context of China's vigorous promotion of its rural revitalization and land transfer policy, land outsourcing is a perspective worthy of attention to understand China's rural land production and agricultural development. Based on rural land outsourcing in China from 2003 to 2015, this study adopts DEA efficiency analysis and Tobit regression analysis to measure the efficiency of rural land outsourcing in China, as well as discussing its influencing factors. The results show that (1) from 2003 to 2015, the efficiency of rural land outsourcing in China has risen, especially in the eastern region, where the efficiency has the best performance. Overall, technical efficiency has hindered the improvement of rural land outsourcing efficiency. (2) The development of rural land outsourcing is restricted by factors such as the newly increased arable land area in rural areas, the foreign labor force, and rural managers, while land outsourcing income cannot significantly promote the expansion of land outsourcing. (3) Large rural agricultural enterprises or co-operatives enhance the efficiency of land outsourcing. Under the food security policy, realizing the technological increment of land outsourcing and land economy can effectively promote the scale and production efficiency of land outsourcing.